Inventario de las plagas y los insectos benéficos del cacao Theobroma cacao L. en el cantón El Pangui, provincia de Zamora Chinchipe. - Guamán Montaño, David Rogelio (2017)
The present research work, entitled “CHECKLIST OF PESTS AND BENEFICIAL INSECTS OF CACAO Theobroma cacao L. IN EL PANGUI CANTON, ZAMORA CHINCHIPE PROVINCE” was developed in the Entomology Laboratory of Universidad Nacional de Loja and in the cacao crops of El Pangui canton, from March to November 2016, with the purpose of identifying and knowing the insect species both pests and beneficial associated to the cacao crop. Seven pest species were recorded, being four of them identified to species level (Monalonion dissimulatum, Xylosandrus morigerus, Steirastoma breve, Toxoptera aurantii), two to genus level (Xyleborus sp., Atta sp.) and one to the family level (Tortricidae). Considering pests’ natural enemies, the family Syrphidae (Ocyptamus sp., Ocyptamus gastrotactus and Pseudodorus sp.) and Coccinellidae (Harmonia sp.) were found attacking Toxoptera aurantii.